Pengembangan Media Pembelajaran Komik Berbasis Science, Technology, Engineering, and Mathematics (STEM) pada Materi Bangun Ruang Sisi Datar Kelas IX - Muhammad Khalvin Fernanda; Ikmawati Ikmawati; Asyril Asyril; Ariantje Dimpudus (De Fermat : Jurnal Pendidikan Matematika, 2026)
This study aims to examine the process of developing Science, Technology, Engineering, and Mathematics (STEM)-based comic learning materials, as well as the validity, practicality, and feasibility of these materials for teaching flat-sided three-dimensional shapes to ninth-grade junior high school students. The study employs a Research and Development (R&D) approach using the ADDIE model, which comprises the Analysis, Design, Development, Implementation, and Evaluation stages. The Analysis stage includes an analysis of needs, curriculum and content, as well as technological developments. The Design stage involves the development of instructional materials, product design, and the creation of research instruments, including expert validation sheets for content, media, and language, as well as a student practicality questionnaire. The Development stage included product creation and expert validation. The Implementation stage was conducted with 31 ninth-grade students. The Evaluation stage involved product revisions by subject matter and language experts. The research results indicated that students struggled to understand the material, highlighting the need for comics as an engaging visual medium. The school implemented the Merdeka Curriculum with this material as the research focus. The validation results were 92% for content, 100% for media, 95.11% for language, and 90.4% for practicality. The 93.38% feasibility percentage indicates that the media is highly valid and suitable for use in mathematics instruction on the topic of flat-sided three-dimensional shapes for 9th-grade junior high school students, following the stages of storyboarding, expert validation of the instructional materials, product revision, and phased, structured pilot testing with students